PENGARUH WAKTU PENGOMPOSAN DAN PERBANDINGAN DEBU SABUT KELAPA DENGAN KOTORAN KAMBING TERHADAP KUALITAS PUPUK ORGANIK - Euis Nurul Hidayah; Dea Maylita Dharmasari Jatmiko (EnviroUS, 2022)
Composting is a process of decomposition of organic matter by utilizing microorganism. This composting uses coconut ash dust and goat manure with the addition of Orgadec bioactivator Manure that has entened the composting process is then analyzed for levels of Nitrogen (N), Carbon (C), pH, Temperature Water Content and C/N Ratio. The results of the analysis are then compared with the quality standarts of SNI 19-7030-2004. Manure analysis was carried out on 7, 14, 21, 28, and 35 days. The results of the analysis of manure with a material variation of 1:1:1 are more effective and require a relatively fast composting time of <30 days, compared to variations of 1:1:0 dan 1:2:1 which require a relatively long decomposition time, namely >35 days.